Structure-activity relationship of CART (cocaine- and amphetamine-regulated transcript) peptide fragments - Maixnerová, Jana; Hlaváček, Jan; Blokešová, Darja; Kowalczyk, Wioleta; Elbert, Tomáš; Šanda, Miloslav; Blechová, Miroslava; Železná, Blanka; Slaninová, Jiřina; Maletínská, Lenka (Peptides, 2007)
CART (cocaine- and amphetamine-regulated transcript) peptides are neuropeptides abundant in the central nervous system and periphery found to be involved in the regulation of food intake behavior and other physiological processes. Recently, we reported specific binding of (125)I-CART(61-102) to the rat adrenal pheochromocytoma cell line PC12, both intact cells and cell membranes. In this study, several fragments of CART(61-102) corresponding to its structural loops were synthesized and tested for their potency in binding experiments using PC12 intact cells and cell membranes and in feeding test with fasted mice. From all shorter peptides tested, only CART(74-86) and CART(62-86) containing disulfide bridges kept partial binding potency of the original molecule with K(i) in 10(-5) and 10(-4)M range. However, these fragments were not able to inhibit food intake after their central administration up to a dose of 4 nmol/mouse. The results showed that a compact structure containing three disulfide bridges is necessary for preservation of full biological activity of CART peptides.
Keywords: financování organizované; Animals; PC12 Cells; sekvence aminokyselin; stravovací zvyklosti; Structure-Activity Relationship; Molecular Sequence Data; Mice; Amino Acid Sequence; myši; proteiny nervové tkáně; peptidové fragmenty; Financing, Organized; molekulární sekvence - údaje; Nerve Tissue Proteins; Male; Peptide Fragments; Feeding Behavior; buňky PC12; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; mužské pohlaví; zvířata; Mice, Inbred C57BL; Rats; myši inbrední C57BL